The Analysis of Community Financial Resilience in Traditional Savings and Loan Practices, Remittances, and Banking Access in East Lombok - Linda Junita Lestari; Sulkiah (LP2M IAIN Palopo, 2026)
Community financial resilience is an important aspect of household welfare, particularly in rural areas where income tends to fluctuate. In East Lombok, many households rely on agriculture and informal economic activities, making them vulnerable to economic shocks. In this context, traditional savings and loan practices, remittances from migrant workers, and access to formal banking services play a crucial role in supporting household financial stability. This study aims to analyze the effect of traditional savings and loan practices, remittances, and banking access on community financial resilience in East Lombok. The research employs a quantitative associative approach using primary data collected through questionnaires distributed to 94 household heads in Rarang Village, Terara District. Data were analyzed using multiple linear regression with the assistance of JASP software, preceded by validity, reliability, and classical assumption tests. The results show that banking access has a positive and significant effect on community financial resilience, while traditional savings and loan practices and remittances have positive but statistically insignificant effects. However, simultaneously these three variables significantly influence community financial resilience. These findings imply that strengthening financial inclusion and improving access to formal financial services can enhance household financial stability, while informal financial mechanisms still function as complementary support for rural communities.